Literature Review : Efektivitas Penggunaan Media Edukasi Gizi Terhadap Peningkatan Pengetahuan Dan Sikap Tentang Gizi Seimbang Pada Siswa Sekolah Dasar - Intan Saraswati (Peneliti.net, 2022)
Balanced nutrition is important for school age children because school age children are the optimal period for social, cognitive and emotional growth. In fulfilling balanced nutrition, it is necessary to pay attention to support the growth and development of school children properly. One of the factors for the low knowledge and attitude of balanced nutrition in elementary school students is the educational method that is lecture and does not use media that helps in receiving information and understanding the information provided. Overcoming health problems can be started with a new understanding of balanced nutrition in primary age children. So that we need a method that can make it easier for students to capture nutritional messages